PERAN MAHASISWA KKN-DR KELOMPOK 205 UINSU BEKERJA SAMA DENGANIKATAN REMAJA MASJID RAYA DALAM MENANAMKAN NILAI MODERASI BERAGAMA DI DESA TALANG KUNING KENAGARIAN RABI JONGGOR KECAMATAN GUNUNG TULEH - Anggun Eci Amelia; Nurhidayah Nurhidayah; Dewi Agustina (STIT AL-AMIN KREO TANGERANG, 2021)
This article aims to find out the socio-religious role played by UINSU KKN-DR 205 students to participate in the activities of the Great Mosque Youth Association in Talang Kuning Kenagarian Rabi Jonggor, Gunung Tuleh District, West Pasaman Regency. Also to find out the factors that support and obstacles that hinder the activities of youth mosques. The author conducted research directly to the research site using observation methods, interviews with community leaders, religious leaders, and teenagers. After the research was conducted, it turned out that the Talang Kuning Great Mosque Youth Association was less active in carrying out social roles because only a few teenagers played an active role in every activity carried out. Besides, it is also hampered by funding problems. Then the researchers gave advice, especially to all youths to participate in and hold mosque youth organization activities, and to community and government leaders to be able to help and support every activity carried out by mosque youth.